Psilocybin and Other Classic Psychedelics in Depression. - Nutt,DJ; Peill,JM; Weiss,B; Godfrey,K; Carhart-Harris,RL; Erritzoe,D (Curr Top Behav Neurosci, 2024)
Psychedelic drugs such as psilocybin and ketamine are returning to clinical research and intervention across several disorders including the treatment of depression. This chapter focusses on psychedelics that specifically target the 5-HT2A receptor such as psilocybin and DMT. These produce plasma-concentration related psychological effects such as hallucinations and out of body experiences, insightful and emotional breakthroughs as well as mystical-type experiences. When coupled with psychological support, effects can produce a rapid improvement in mood among people with depression that can last for months. In this chapter, we summarise the scientific studies to date that explore the use of psychedelics in depressed individuals, highlighting key clinical, psychological and neuroimaging features of psychedelics that may account for their therapeutic effects. These include alterations in brain entropy that disrupt fixed negative ruminations, a period of post-treatment increased cognitive flexibility, and changes in self-referential psychological processes. Finally, we propose that the brain mechanisms underlying the therapeutic effect of serotonergic psychedelics might be distinct from those underlying classical serotonin reuptake-blocking antidepressants.